A novel ballonet polishing tool and its robot control system for polishing the curved surface of mould. (1st October 2007) - Ji, S.M.; Zhang, L.; Yuan, Q.L.; Jin, M.S.; , J.L. Yuan
The curvature of polishing tool is not often accordant with the polished surface in polishing the curved surface of mould so that usually the smaller polishing tools are used for adapting the curvature change of the workpiece. A small polishing tool has often low polishing efficiency because of small contact area with the surface of workpiece. A larger rigid polishing tool often cannot have a good contact state with variable curved surface. In order to improve the efficiency and quality for the polishing curved surface of mould, a novel type of ballonet polishing tool is developed. The tool has a flexible ballonet covered polishing cloth in its head, which is of nicer flexibility so that it can accord with the variable curvature of curved surface of mould by controlling the air pressure of the ballonet. The advantage of the tool is that it has larger and submissive contact area with the polished surface in polishing so that it has higher polishing efficiency and also better polishing surface roughness and local curvature precision. In this paper, the principle of the tool and the robot system for controlling the pose of the tool are introduced. The simulation of the polishing track and the polishing experiment are achieved. In a polishing example, we obtain an Ra of 0.042 ?m surface roughness.